UV-B Induces Chloroplast Movements in a Phototropin-Dependent Manner - Hermanowicz, Paweł; Banaś, Agnieszka Katarzyna; Sztatelman, Olga; Gabryś, Halina; Łabuz, Justyna (Frontiers in Plant Science, 2019)
We examined the impact of UV-B irradiation on chloroplast movements in Arabidopsis leaves. Directional chloroplast movements induced by blue light have been described in multiple plant species. In weak light, chloroplasts accumulate at periclinal cell walls to increase light capture. In strong light, chloroplasts exhibit the avoidance response, as they move towards anticlinal walls to protect the photosynthetic apparatus from light-induced damage. In Arabidopsis, chloroplast movements are triggered by phototropins, phot1 and phot2, which are known as blue/UV-A photoreceptors. We found that irradiation with UV-B of 3.3 µmol·m-2·s-1 induced chloroplast accumulation in wild type plants. UV-B triggered accumulation was dependent on the presence of phototropins, especially phot1, but not on UVR8 (the canonical UV-B photoreceptor). Irradiation with strong UV-B of 20 µmol·m-2·s-1 did not induce substantial chloroplast relocations in wild type leaves. However, in the jac1 mutant, which is defective in chloroplast accumulation, strong UV-B elicited chloroplast avoidance. This indicated that UV-B can also activate signaling to the avoidance response. To assess the possibility of indirect effects of UV-B on chloroplast movements, we examined the impact of UV-B on the actin cytoskeleton, which serves as the motile system for chloroplast movements. While irradiation with UV-B of 3.3 µmol·m-2·s-1 did not affect the actin cytoskeleton, strong UV-B disrupted its structure as shown using an Arabidopsis line expressing Lifeact-GFP. In wild type plants, pre-treatment with strong UV-B attenuated chloroplast responses triggered by subsequent blue light irradiation, further indicating that this UV-B intensity also indirectly affects chloroplast movements. Taken together, our results suggest that the effect of UV-B on chloroplast movement is twofold: it directly induces phototropin-mediated movements, however, at higher intensities, it attenuates the movements in a non-specific manner.